Situation Report: Czechoslovakia, 16 July 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Membership Figures…and Problems Stamping Out Economic Crime: An Uphill Task Labor Morale: Criticism that Needs Criticism Historical Fiction with a Nonfictive Charge